Parasitic Helminths and Zoonoses - From Basic to Applied Research 2022
DOI: 10.5772/intechopen.102882
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Integrated Root-Knot Nematodes (Meloidogyne) Management Approaches

Abstract: Meloidogyne genus contains the most prevalent and harmful worms formally known as root-knot nematode species. They attack a wide range of plants belonging to different plant families. The infective second stage juveniles (J-II) feed on the roots and as a result, the host plant roots become swollen/produce galls. The attack plant shows stunted growth and in extreme cases, the death of the plant occurs. An integrated pest management (IPM) approach is required to tackle these harmful nematodes spp. The integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Traditionally, nematode management has been heavily relied on the use of synthetic nematicides [4]; however, it has been revealed that a significant number of these nematicidal products present substantial risks to both human health and the environment. As a result, several of these nematicides have been banned [5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, nematode management has been heavily relied on the use of synthetic nematicides [4]; however, it has been revealed that a significant number of these nematicidal products present substantial risks to both human health and the environment. As a result, several of these nematicides have been banned [5].…”
Section: Introductionmentioning
confidence: 99%